Documentation of lead exposure-associated comorbidity among 4538 workers in China - Qian Hua; Pingyang Zhang; Yong Yang; Jingchao Ren; Shouming Cui; Yuxin Yang; Loulou Cai; Jia Ding; Shouyuan Cui; Mingyang Gao; David C. Christiani; William Au; et al. (BMC Public Health)
Abstract Background Systematic documentation of morbidity with exposure assessment in a large group of lead (Pb)-exposed workers in China. Methods Using the cluster sampling method, Pb-exposed workers were recruited from a factory in the Henan Province, China. The morbidity information and blood lead concentration (BLC) from each worker were collected. Relationships between the two sets of data were analyzed using the logistic regression and restricted cubic spline (RCS) models. Results Among the 4538 recruited workers, there were 2780 males and 1758 females, with a median age of 34 years old, and BLC ranging from 7.70 to 722.70 μg/l. Among them, 1247 (27.4%) had multiple morbidities (comorbidity). Those with the highest BLC showed a 1.79-fold (significant) increase in comorbidities compared to those with the lowest BLC (95% confidence interval = 1.43, 2.25; p < 0.001). In addition, the comorbidities exhibited a BLC dose–response relationship (p < 0.001), after adjusting for potential confounding factors. The RCS curve analysis revealed a nonlinear relationship between BLC and risk of comorbidity (p-overall < 0.001, and p-nonlinear < 0.001). Sensitivity analysis further confirmed the dose–response relationship between BLC and the risk of developing comorbidities. Additionally, the data indicate that female workers were more susceptible to comorbidities. Conclusion Our study demonstrates that comorbidity was prevalent and was dose-dependent among lead exposed workers.